2020
DOI: 10.1038/s41467-020-19544-9
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-domain ultrafast passive logic: NOT and XNOR gates

Abstract: Electronic Boolean logic gates, the foundation of current computation and digital information processing, are reaching final limits in processing power. The primary obstacle is energy consumption which becomes impractically large, > 0.1 fJ/bit per gate, for signal speeds just over several GHz. Unfortunately, current solutions offer either high-speed operation or low-energy consumption. We propose a design for Boolean logic that can achieve both simultaneously (high speed and low consumption), here demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…As a kind of the crystalline porous materials with structural tunability and functional versatility, luminescent metal-organic frameworks (MOFs) [21][22][23][24][25][26][27][28] have been considered as promising candidates for optical sensors. They not only offer the advantages of high sensitivity, fast response, simple operation and low cost as fluorescent sensors, [29][30][31][32][33][34][35] but can also be designed to perform Boolean logic operations [36][37][38] to transmit and process information, just like the human brain and electronics. Additionally, intelligent, decision-based molecular logic devices show great potential for life science applications.…”
Section: Introductionmentioning
confidence: 99%
“…As a kind of the crystalline porous materials with structural tunability and functional versatility, luminescent metal-organic frameworks (MOFs) [21][22][23][24][25][26][27][28] have been considered as promising candidates for optical sensors. They not only offer the advantages of high sensitivity, fast response, simple operation and low cost as fluorescent sensors, [29][30][31][32][33][34][35] but can also be designed to perform Boolean logic operations [36][37][38] to transmit and process information, just like the human brain and electronics. Additionally, intelligent, decision-based molecular logic devices show great potential for life science applications.…”
Section: Introductionmentioning
confidence: 99%
“…Towards efficient and high-speed signal processing, photonic schemes based on all-pass (or phase-only) linear spectral filtering have attracted considerable recent interest. These schemes offer a simple and passive solution to realize a multitude of important functionalities, such as ultrafast logic gates 16 , ultrahigh-speed spectroscopy 17 , quantum states manipulation 18 , 19 , microwave photonics operations 20 , neuromorphic computing 13 , pulse shaping and arbitrary waveform generation 21 , 22 , among many others. The key advantage of linear spectral phase-only optical filtering is that it enables implementation of the desired functionality at speeds commensurate with a photonic solution while preserving the full energy of the processed temporal signal.…”
Section: Introductionmentioning
confidence: 99%
“…However, all the current alternative techniques fail to provide the required performance, compared to electronic logic gates, simultaneously in three important aspects: energy consumption, footprint, and operation speed. Passive optical logic gate designs based on spectral phase filtering have been demonstrated that enable ultrafast operation with potential minimal power consumption 16 , but their previous implementations still necessitate of a bulky and active waveshaper.…”
Section: Introductionmentioning
confidence: 99%
“…As in electronic computing, the power consumption and embodied energy supply are also the challenges in mechanical computing 22 . Designing self-powered logic gates can expand its application scenarios, especially for self-powered environmental interaction.…”
Section: Introductionmentioning
confidence: 99%